2018
DOI: 10.3390/chemengineering2010003
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Temporal Variation of a Full-Scale Horizontal Constructed Wetland in Reducing Nitrogen and Phosphorus from Domestic Wastewater

Abstract: Abstract:Cultural eutrophication stimulated by anthropogenic-derived nutrients represents one of most widespread water quality problems worldwide. Constructed wetlands (CWs) have emerged as an aesthetic, sustainable form of wastewater treatment, but, although they have shown adequate levels of organic matter removal in wastewaters, the effectiveness of nutrient removal has been less successful. An eleven-month monitoring program was undertaken in a horizontal subsurface flow CW (HSSF-CW) treating domestic wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…The release of antibiotics (such as phytometallophores and phytochelatins) by the roots of plants [83], plant cover, settlement of microorganisms, exposure to abiotic stress conditions such as pH, temperature, and oxygen concentration can play important roles in the reduction of coliforms [84,85]. In addition, many of these factors are interrelated [86][87][88].…”
Section: Fecal Coliformsmentioning
confidence: 99%
“…The release of antibiotics (such as phytometallophores and phytochelatins) by the roots of plants [83], plant cover, settlement of microorganisms, exposure to abiotic stress conditions such as pH, temperature, and oxygen concentration can play important roles in the reduction of coliforms [84,85]. In addition, many of these factors are interrelated [86][87][88].…”
Section: Fecal Coliformsmentioning
confidence: 99%
“…Overall, this study showed that large‐scale HSSF CWs with either gravel or slag as substratum, could achieve comparable pollutant removal efficiencies and provide a feasible solution for remediation of polluted urban water. Mesquita et al (2018) reported inadequate removal of nutrients from HFCW used for secondary treatment of domestic wastewater. The reason was seasonal temperature variation, high HLR, and low HRT.…”
Section: Materials Study In Cwsmentioning
confidence: 99%
“…The focus is being placed on process optimization, rather than on cost-saving [2,5]. There is still a need for more information regarding nutrient removal, polishing treatments and operational costs of nature-based wastewater treatment technologies, as noted in studies [6][7][8][9][10][11][12][13]. Although there is a wide variety of chemical and biological technologies for nutrient removal, these processes normally entail high operational and investment costs that narrow profit margins.…”
Section: Introductionmentioning
confidence: 99%
“…It is often necessary to include artificial aeration or chemical additions for improving treatments, which leads to high energy consumption besides being ineffective for carbon sequestration. By contrast, natural solutions based on constructed wetlands have proved to be very effective in removing organics and nitrogen, but still require energy consumption for effluent recirculation and evapotranspiration dependence [7,8].…”
Section: Introductionmentioning
confidence: 99%